2020
DOI: 10.1200/jco.20.02110
|View full text |Cite
|
Sign up to set email alerts
|

Longer Follow-Up Confirms Recurrence-Free Survival Benefit of Adjuvant Pembrolizumab in High-Risk Stage III Melanoma: Updated Results From the EORTC 1325-MG/KEYNOTE-054 Trial

Abstract: PURPOSE We conducted the phase III double-blind European Organisation for Research and Treatment of Cancer (EORTC) 1325/KEYNOTE-054 trial to evaluate pembrolizumab versus placebo in patients with resected high-risk stage III melanoma. On the basis of 351 recurrence-free survival (RFS) events at a 1.25-year median follow-up, pembrolizumab prolonged RFS (hazard ratio [HR], 0.57; P < .0001) compared with placebo. This led to the approval of pembrolizumab adjuvant treatment by the European Medicines Agency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 33 publications
8
177
1
6
Order By: Relevance
“…Analogously, pembrolizumab for high-risk stage III melanoma resulted in significantly longer RFS than placebo, with no new toxic effects reported and no differences according to the BRAF status. The 3-year RFS rate was 63.7% for pembrolizumab versus 44.1% for placebo with a HR of 0.56 (95% CI, 0.47 to 0.68) [ 83 ] ( Table 3 ). The combination of nivolumab and ipilimumab has also been investigated in the adjuvant setting.…”
Section: Braf Mutations As Pharmacological Targets In Melanomamentioning
confidence: 99%
“…Analogously, pembrolizumab for high-risk stage III melanoma resulted in significantly longer RFS than placebo, with no new toxic effects reported and no differences according to the BRAF status. The 3-year RFS rate was 63.7% for pembrolizumab versus 44.1% for placebo with a HR of 0.56 (95% CI, 0.47 to 0.68) [ 83 ] ( Table 3 ). The combination of nivolumab and ipilimumab has also been investigated in the adjuvant setting.…”
Section: Braf Mutations As Pharmacological Targets In Melanomamentioning
confidence: 99%
“…In addition, the toxicity profile of nivolumab was favourable compared to ipilimumab. Further data to support adjuvant PD‐1 inhibitor treatment were seen in the Keynote‐054 trial, which showed an RFS benefit of adjuvant pembrolizumab for up to 1 year compared with placebo in patients with resected Stage III melanoma 46,47 . The OS results are eagerly awaited.…”
Section: Systemic Therapy Standards and Updatesmentioning
confidence: 99%
“…Im klinischen Alltag sind diese Konzepte, insbesondere in Akutsituationen, oft schwer voneinander zu differenzieren. Pembolizumab‐assoziierte Grad 3–5 irAE wurden mit einer Häufigkeit von 31,6 % berichtet [1]. Die Autoimmunhepatitis tritt im Median 1,3 Monate mit einem dokumentierten Mindestzeitraum von acht Tagen nach Administration auf.…”
Section: Kommentarunclassified